Proposed antecedents of workplace incivility in the service sector - Lim, Hui Ling; Mohd Shamsudin, Faridahwati; Sri Ramalu, Subramaniam (2014)
In the context of service sector, uncivil behaviour toward customers is likely to harm the effectiveness of the service provider.Built upon the stressor-emotion model of counterproductive work behaviour developed by Spector and Fox (2005), we attempt to explain workplace incivility in this context by proposing that role stress (role conflict and role ambiguity) and interactional justice (interpersonal justice and informational justice) may provoke uncivil behaviours through the mediation of negative emotions. In addition, we propose that self monitoring may play a role in moderating the relationship between negative emotions and workplace incivility.